Analisis Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Minat Nasabah Menabung pada PT. BSI Cabang Padangsidimpuan - Ali Hardana; Jafar Nasution; Arti Damisa (Universitas Muhammadiyah Surabaya, 2022)
Customer interest is a high-value asset for banks, if customer interest increases, profits also increase. But in fact, customers complain about the services provided by the bank because it is not in accordance with customer expectations. The formulation of the problem in this study is whether there is an effect of product quality and service quality both partially and simultaneously on the interest of customers in PT Bank Syariah Mandiri Branch in Padangsidimpuan. The discussion of this research relating to product quality and service quality to customers is interesting. In connection with that, the approach taken is theories related to product quality, service quality, and customer interest. Service is any action or activity that can be offered by a party to another party, which is basically intangible and does not result in any ownership. This study uses a quantitative research approach, data collection techniques include questionnaires, with as many as 56 respondents as customers. The analysis used in this study is validity test, reliability test, descriptive analysis, normality test, linearity test, determination test (R2), multiple linear regression, t-test, and f test. The results obtained showed that the value of R Square was 0.785 or 78.5%. The T-test shows there is a significant influence between product quality on the interest of customers to save at PT. Bank Syariah Mandiri Padangsidimpuan Branch. Likewise, there is an influence between the quality of service to the interests of customers saving at PT. Bank Syariah Mandiri Padangsidimpuan Branch. The F test shows that simultaneously product quality and service quality have a significant effect on the interests of customers saving at PT. Bank Syariah Mandiri Padangsidimpuan Branch.